Trade Restrictions versus Russia Will Put Stress on German Sectors and States Differently - Mario Jung (Wirtschaftsdienst)
Abstract Regarding current trade data, the German economy is not that dependent on their export business with Russia. However regarding imports, risks are clustered due to a high dependence on imports of energy and other raw materials that are not easy to substitute. These risks are also common in all German states. This article also analyses the trade relations of the German states with Russia, presenting the special and unique risks of severe trade disruptions with Russia for the individual German states.